2018
DOI: 10.1002/acn3.654
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibitors in the onset of myasthenia gravis with hyperCKemia

Abstract: Immune checkpoint inhibitors sometimes cause neuromuscular adverse events. Although a few cases of myasthenia gravis with hyperCKemia triggered by immune checkpoint inhibitors have been described, conclusive evidence remains limited. We conducted a systematic review of published cases of myasthenia gravis with hyperCKemia related to immune checkpoint inhibitors. Moreover, we tested anti‐striational antibodies in the case of myasthenia gravis with myositis after nivolumab administration. We located 17 published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 42 publications
(42 reference statements)
2
24
0
1
Order By: Relevance
“…It is known that anti‐titin antibody is accompanied with myositis . Moreover, myasthenia gravis with hyperCKemia is suspected to have a more complicated prognosis than in myasthenia gravis without hyperCKemia; thus, before ICI treatment, AChR antibodies and anti‐striational antibodies should be measured if available . There is a possibility that patients already have subclinical myasthenia gravis, and ICIs are considered the triggering factors of flare‐up, but more studies are needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that anti‐titin antibody is accompanied with myositis . Moreover, myasthenia gravis with hyperCKemia is suspected to have a more complicated prognosis than in myasthenia gravis without hyperCKemia; thus, before ICI treatment, AChR antibodies and anti‐striational antibodies should be measured if available . There is a possibility that patients already have subclinical myasthenia gravis, and ICIs are considered the triggering factors of flare‐up, but more studies are needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…39 StrAbs are regarded as possible biomarkers of irAEs, and it is recommended that they be evaluated in the guidelines published by the American Society of Clinical Oncology. 42,43 F I G U R E 1 A 65-year-old man with non-small cell lung cancer was treated with nivolumab monotherapy, and developed myasthenia gravis and myocarditis. (a) A cardiac muscle biopsy showed lymphocyte infiltration of the myocardium with much greater infiltration of CD8 + T cell lymphocytes than CD4 + T cells.…”
Section: Immune-rel Ated Adver S E E Ventsmentioning
confidence: 99%
“…There are several previous reports of pembrolizumab-associated MG with myopathy. [6][7][8] Takamatsu et al 9 reported 17 cases of MG with hyperCKemia associated with ICIs. In most cases, respiratory failure or worsening of MG symptoms was noted immediately after MG onset, while death occurred in some cases.…”
Section: Jcnmentioning
confidence: 99%